Value theory and business cycles - McCracken, Harlan Linneus ([New York]: Falcon Press, 1933)
This is an evaluation of representative economic writings from Adam Smith to the present time (1933), dealing with the theories advanced in one general field-the field of value theory and business cycles. It aims at showing the vital relation between business cycle theory and value theory. The writings of note (of that period) are studied in this book and in each case the theories of business cycles and value are examined from (1) the standpoint of logic and (e) in a number, from the standpoint of historical accuracy.
"References cited in footnotes": p. 263-264.
lje 24/01/2018
Loans
Keywords: Value; Business cycles; Prices; Currency question